Epidermal growth factor receptor tyrosine kinase inhibitors in previously treated advanced non-small-cell lung cancer with wild-type EGFR. (22nd January 2016) - Mitsuoka, Shigeki; Kawaguchi, Tomoya; Kubo, Akihito; Isa, Shun-ichi; Asai, Kazuhisa; Uji, Masato; Watanabe, Tetsuya; Sawa, Kenji; Yoshimoto, Naoki; Oka, Takako; Nakai, Toshiyuki; Suzumura, Tomohiro; et al.
ABSTRACT: Introduction : While epidermal growth factor receptor (EGFR) – tyrosine kinase inhibitors (TKIs) lead to longer progression-free survival (PFS) when compared with conventional chemotherapy in non-small-cell lung cancer (NSCLC) harboring activating EGFR mutations, the role of EGFR-TKI remains unclear in EGFR-wild-type (WT) NSCLC. Areas covered : This article reviews selected data from randomized trials regarding the use of TKIs in EGFR-WT NSCLC. Nine randomized phase III trials have compared EGFR-TKI with chemotherapy in NSCLC patients in a second or later line setting. Two of these trials, TAILOR and DELTA, which were designed to investigate treatment benefits according to EGFR genotype, demonstrated that docetaxel chemotherapy displayed significantly better in progression-free survival (PFS) when compared with the EGFR-TKI erlotinib. Biomarkers to predict clinical benefits of the drug against EGFR WT tumor, and the efficacy of combination regimens using erlotinib or single-use afatinib against tumors are also covered in this article. Expert opinion : Considering the modest benefits of erlotinib for EGFR-WT tumors, future studies are warranted, including the exploration of useful biomarkers and new treatment strategies for EGFT-TKI use, as well as the development of more sensitive EGFR mutation tests.